Two Co(II) coordination polymers: crystal structures and anti-ovarian cancer activity by inducing the ROS genes expression. Issue 4 (14th March 2022) - Yang, Dong-Mei; Huang, Li-Hong; Xia, Qiong; Li, Ai-Ling; Chen, Yu
Abstract: Two new unsymmetrical ligands, namely, 2-(pyridin-3-yl)-5-(quinolin-2-yl)-1, 3, 4-oxadiazole (L1) and 2-(pyridin-4-yl)-5-(quinolin-2-yl)-1, 3, 4-oxadiazole (L2), have been synthesized and their self-assembly reactions with Co(NO3 )2 and Co(ClO4 )2 have been investigated for the rational construction of coordination polymers (CPs). It was found that the counter-anion plays an important role in the structural assemblies. Their anti-ovarian cancer activity was evaluated and the related mechanism was explored at the same time. Firstly, the proliferation of the ovarian cancer cells was measured with CCK-8 detection kit. Then, the real time RT-PCR was used to evaluate the relative expression levels of the ROS related genes in the ovarian cancer cells after compounds treatment.